Jean-Luc Nancy: przyjemność (w) dekonstrukcji - Kowalik, Bartosz (Przestrzenie Teorii, 2023)
The article deals primarily with the concept of pleasure in Jean-Luc Nancy’s thought. It occurs in many texts by the philosopher and connects with key concepts of his deconstructive project: the body, relational ontology and the writing. For Nancy, pleasure is, among other things, a particular somatic experience, the effect of peculiar writing practice, and finally, the experience of non-identity of a singular plural subject. The distinctive feature of pleasure (in various conceptualizations) is the opening that it makes every time, which Nancy derives from his deconstructive considerations on the works of Freud, Kant and Barthes. In the thesis, Nancy’s revised concept of pleasure as an opening is also referenced to Derrida’s thought in order to analyse the general relations between pleasure and deconstruction and to consider how deconstruction can be a source of pleasure.